Spontaneous Appearance and Transmission of Polydactyly in Dexter Cattle - Richard Browning Jr.; Emily G. Hayes; Andrea S. Lear (Case Reports in Veterinary Medicine)
A 3-yr-old Dexter cow and her yearling Dexter heifer calf exhibited polydactyly. Neither animal was linebred within 5 generations. This cow-calf pair represented the first reported occurrence of polydactyly in Dexter cattle in the US or abroad. Based upon external examination, the cow was classified as having a spontaneous unilateral case of polydactyly with an extra digit along the medial digit of the right front limb and the heifer was classified as having bilateral polydactyly because both front limbs exhibited an extra digit along the medial digit. Radiographic examination confirmed bilateral status of the heifer and revealed bilateral status of the cow. The front feet of the cow and heifer had extra bone formation consistent with an extra digit along the medial digit. Neither animal suffered from limited mobility to date or required hoof treatments. The cow produced a second calf from a different sire, a bull calf that did not appear polydactylous per external examination and was not examined radiographically. The two polydactylous animals will remain in the breeding herd to produce more study calves unless their fitness becomes compromised. Genetic aspects of the cases are discussed.